1987
DOI: 10.1021/bi00378a026
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor dependent phosphorylation of a 35-kilodalton protein in placental membranes

Abstract: In human placental membranes isolated in the presence of ethylenediaminetetraacetic acid (EDTA), epidermal growth factor (EGF) stimulated the [gamma-32P]ATP-dependent phosphorylation of tyrosine residues on the 170-kilodalton (kDa) EGF receptor and on a 35-kDa protein. The initial rate of phosphorylation of these proteins in the presence of EGF was 5.2 and 3.5 nmol of phosphate min-1 (mg of receptor protein)-1, and this was approximately 10- and 6-fold higher than the basal rate, respectively. Half-maximal pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 57 publications
3
22
1
Order By: Relevance
“…The effect on vesicle aggregation of EGF receptor-catalyzed tyrosine phosphorylation at Tyr-21, on the other hand, has not been elucidated, although it seems clear that this phosphorylation decreases the Ca21 concentration required for phospholipid binding Ando et al, 1989). Moreover, phosphorylation by the EGF receptor converts a certain form of annexin I, which remains associated with membranes_prepared from human placenta in the absence of Ca , into a Ca2+-regulated form whose membrane association is sensitive to chelation of the divalent cation (Sheets et al, 1987). The MVBs of NIH 3T3 cells expressing the human EGF receptor also contain a Ca2 -insensitive form of annexin I, which is rendered Ca2+-sensitive upon phosphorylation by the receptor kinase.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on vesicle aggregation of EGF receptor-catalyzed tyrosine phosphorylation at Tyr-21, on the other hand, has not been elucidated, although it seems clear that this phosphorylation decreases the Ca21 concentration required for phospholipid binding Ando et al, 1989). Moreover, phosphorylation by the EGF receptor converts a certain form of annexin I, which remains associated with membranes_prepared from human placenta in the absence of Ca , into a Ca2+-regulated form whose membrane association is sensitive to chelation of the divalent cation (Sheets et al, 1987). The MVBs of NIH 3T3 cells expressing the human EGF receptor also contain a Ca2 -insensitive form of annexin I, which is rendered Ca2+-sensitive upon phosphorylation by the receptor kinase.…”
Section: Discussionmentioning
confidence: 99%
“…This pool of lipocortin is significant as Carnuccio et al (1981) and Cirino & Flower (1987b) reported that it is the external membrane-associated lipocortin 1 that produces its biological effects. Furthermore, the models in which lipocortin 1 has been shown to have biological activity are those in which the protein has been applied externally (Cirino & Flower, 1987a;Cirino et al, 1987;Davidson et al, 1991 (Sheets et al, 1987) and in porcine heart (Pula et al, 1990) and A431 cells (Ando et al, 1991). In the first two examples, lipocortin 1, and 5 and 6 respectively could be extracted by non-ionic detergents but not by EGTA, and hence resemble the membrane-bound pools observed in elicited cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this report we add placental endonexin II to this growing list. Lipocortin 1 (5,14,15,30) and calpactin I (5) have been shown to be abundant placental proteins and immunological data suggest that endonexin I is also present (D.D.S. and H.T.H., unpublished results).…”
Section: Kpsrlydayelkhalkgagtnekvlteiiasrtpeelraikqvyeewmentioning
confidence: 93%